Análisis del conocimiento de la política pública y el Buen Vivir de los estudiantes del primer semestre de la carrera de Pedagogía de las Ciencias Experimentales de la Facultad de Ciencias de la Educación, Humanas y Tecnologías, período octubre 2017- marzo 2018. - Ashqui Ashqui, Abdon Geovanny (2018)
The research aims to establish the level of knowledge of public policy and good living of the students of first semester of the career of Pedagogy Career of the Education, Humans and technologies Sciences Faculty, in which evidenced that 53% do not know the obligations of the state. The diagnosis was used and was not experimental; type of research was field, descriptive, bibliographic, across-sectional; with a diagnosis level. The method used was inductive, deductive. We worked with the population of the student of the National University of Chimborazo, the type of sampling was not probabilistic or intentional, we worked with 19 students; the technique was the survey to collect the data, the instrument was the questionnaire for the analysis and interpretation which led us to get the conclusion that the educational policy and good living, promote all rights with culture and good customs for a better quality development. Finally, it is recommended to implement training that involves the enrichment of ancestral knowledge for better professional development and quality of life in educational training within the Career.